A Novel Heterozygous Variant in F2 Gene in a Chinese Patient With Coronary Thrombosis and Acute Myocardial Infarction Leads to Antithrombin Resistance - Tang, Yi; Zhang, Liyang; Xie, Wenlin; Jin, Jieyuan; Luo, Yujiao; Deng, Mingyang; Liu, Zhengyu; Pan, Hong Wei; Zhang, Yi; Zheng, Zhaofen; Fan, Liang-Liang (Frontiers in Genetics, 2020)
Thrombophilia refers to a group of conditions where the blood clots more easily than normal. These blood clots can cause problems such as deep vein thrombosis or pulmonary embolism. Most kinds of mutated coagulation factors II (F2) exhibit lower procoagulant activity, but in some cases, a higher coagulation rate has been observed. The underlying mechanism is that those variations can prevent F2s from being inhibited by antithrombin, leading to a contiguous activation of procoagulation, and causing recurrent thromboembolism. In this study, a patient was admitted to our hospital due to repeated chest pain for two days and aggravated for four hours. A medical history investigation showed that he had three deep venous thromboses in the lower limbs and one portal vein thrombosis events during the past ten years. The electrocardiogram showed Q wave elevation and slight ST segment elevation in lead V2, and coronary angiogram showed a total occlusion of the left anterior descending artery. Laboratory testing found that troponin I was obviously elevated. Family history also indicated that both his father (II-3) and grandfather (I-1) died from pulmonary thromboembolism. Whole-exome sequencing was performed to detect the genetic lesion of the patient, and a novel mutation (c.1621 C>T/p.R541W) of F2 was identified in the patient. This novel mutation resulted in a substitution of arginine by tryptophan, leading to antithrombin resistance (ATR). Our study is consistent with previously published papers. In conclusion, this study not only identifies a novel mutation of F2 and will contribute to the genetic diagnosis and counseling of families with thrombosis but also suggests that the site p.R541 of F2 may play a crucial role in thrombosis.